The Influence of Organizational Climate on Employee Commitment With Job Satisfaction and Motivation as Intervening Variables at Pt. Persada Engineering Media - Riswan Sidik; Abdi Sugiarto (Yayasan Multidimensi Kreatif, 2024)
A conducive organizational climate and its influence on employee performance, job satisfaction, motivation, and commitment are essential in improving organizational performance. The purpose of this study is to find out and analyze the influence of organizational climate on employee commitment mediated by job satisfaction and motivation at PT. Media Teknik Persada. This research was conducted with a causal associative quantitative approach. The sample used was all employees at PT. Media Teknik Persada with a total of 67 people. The results of data analysis of this study show that the organizational climate has no influence on employee commitment with a T-statistical value of 0.416 < 1.96 and a P-value of 0.678 > 0.05). However, a conducive organizational climate had a positive and significant effect on job satisfaction with a T-statistical value of 18.076 > 1.96 and a P-value of 0.000 < 0.05 and motivation with a T-statistical value of 11.773 > 1.96 and a P-value of 0.000 < 0.05. Job satisfaction had no effect on employee commitment with a T-statistical value of 0.901 < 1.96 and a P-value of 0.371 > 0.05. Job satisfaction was also unable to intervene in the influence of organizational climate on employee commitment with a T-statistical value of 0.912 < 1.96 and a P-value of 0.365 > 0.05). On the other hand, work motivation had a positive and significant influence on employee commitment with a T-statistical value of 5.802 > 1.96 and a P-value of 0.000 < 0.05) and was able to intervene in the influence of organizational climate on employee commitment with a T-statistical value of 4.401 > 1.96 and a P-value of 0.000 < 0.05). These findings imply that organizations need to improve, pay attention to, maintain, and improve the organizational climate to create a comfortable atmosphere for employees, which in turn increases employee motivation and commitment.